APLIKASI TES PERSONALITY PLUS BERBASIS WEB - Tadhan, Tadhan; Purba, Florensa Rosani (Teknik dan Ilmu Komputer, 2012)
Understanding human characteristics requires broad knowledge and time consuming tests so that people are reluctant to do it. The current information technology can provide solutions to create a test application that can be done directly by the user. This application is very useful as it can build a userÃ¢â¬â¢s character after taking a personality test. ÃÂ Keywords:ÃÂ  personality test, website